Neurons in the dorsomedial medulla contribute to swallow pattern generation: Evidence of inspiratory activity during swallow. - Teresa Pitts; Ivan Poliacek; Melanie J Rose; Mitchell D Reed; Jillian A Condrey; Hsiu-Wen Tsai; Guannan Zhou; Paul W Davenport; Donald C Bolser (PLoS ONE)
Active contraction of the diaphragm and other inspiratory pump muscles during swallow create a negative thoracic pressure to improve the movement of the bolus (food/liquid) into the esophagus. We tested the hypothesis that dorsomedial medullary inspiratory neurons, including the nucleus tractus solitarius (NTS, pre-motor to the phrenic) would be active during swallow induced by oral water infusion. We recorded neurons in the NTS and medial reticular formation in anesthetized spontaneously breathing cats, and induced swallow by injection of water into the oropharynx. Our results indicate that: 1) a majority of inspiratory cells in the dorsomedial medulla are active during swallow, 2) expiratory neurons are present in the medial reticular formation (deeper to the NTS) in unparalyzed cats and a majority of these cells decreased firing frequency during swallow. Our findings suggest that the dorsomedial medulla is a source of inspiratory motor drive during swallow and that a novel population of breathing-modulated neurons that also are modulated during swallowing exist in the medial reticular formation in unparalyzed animals.